2017
DOI: 10.5817/cp2017-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing online research: Experiences from research concerning cyber-victimisation of people with disabilities

Abstract: The victimisation of people living with disabilities and chronic conditions is a documented phenomenon. It ranges from harassment incidents to disability hate crimes, and causes physical, mental and psychosocial consequences. The Internet has further reshaped this phenomenon which lead to "cyber-victimisation" experiences, with no less impact upon victims. This methodology paper focuses mainly on the challenges and implications of using online methods in a UK-based study exploring the impact of cyber-victimisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
0
12
0
2
Order By: Relevance
“…Geographical and physical accessibility barriers to face-to-face participation, often faced by PWD, are reduced (Deakin & Wakefield, 2014; Moore et al, 2015; Sullivan, 2012; Suri & Patel, 2019; Turney & Pocknee, 2005). Additionally, online methods can promote inclusivity of vulnerable adults and marginalized groups by minimizing social and emotional barriers (Alhaboby et al, 2017; Mann & Stewart, 2000). However, online research excludes those without access to the internet and a level of technological competence (Jowett et al, 2011), and internet access is not equally distributed across the population (Granello & Wheaton, 2004; Helsper, 2008; Oringderff, 2004).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographical and physical accessibility barriers to face-to-face participation, often faced by PWD, are reduced (Deakin & Wakefield, 2014; Moore et al, 2015; Sullivan, 2012; Suri & Patel, 2019; Turney & Pocknee, 2005). Additionally, online methods can promote inclusivity of vulnerable adults and marginalized groups by minimizing social and emotional barriers (Alhaboby et al, 2017; Mann & Stewart, 2000). However, online research excludes those without access to the internet and a level of technological competence (Jowett et al, 2011), and internet access is not equally distributed across the population (Granello & Wheaton, 2004; Helsper, 2008; Oringderff, 2004).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Yet, it has been suggested that the removal of non-verbal cues and need for transcriptions in email-interviewing and text-based focus groups could reduce the researcher bias during interpretation, thus yielding a more authentic representation (Bampton & Cowton, 2002; Jamison et al, 2018; Seymour, 2001). Additionally, it has been implied that more authentic narratives can be seen in text-based online research due to the sense of anonymity in online interactions (Alhaboby et al, 2017; Bargh et al, 2002; Ellison et al, 2006). The relative anonymity of text-based methods arguably encourages disclosure (Egan et al, 2006; Jamison et al, 2018; Joinson, 2005; Shepherd, 2003), and therefore text-based methods may be better suited to discussing sensitive topics (Forrestal et al, 2015; McCoyd & Kerson, 2006).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Just as social inequalities shape digital inequalities, they also affect vulnerability to cybercrime. Connected individuals with disabilities, for example, are disproportionately subjected to harassment, stalking, bullying, and disability-related hate crimes in cyberspace (Alhaboby, et al, 2017). As we will see in the next section, cybercrime disproportionately victimizes members of disadvantaged groups, who are typically less skilled yet more likely to use unsecured (often free) networks that may expose them to cyberthreats.…”
Section: Digital Intersections With Criminal Justice and Securitymentioning
confidence: 99%
“…Internationally, higher rates of victimization have been reported for people with intellectual disabilities, related to violence, injury, abuse and sexual crimes, 42,43 personal and property offenses, and crimes of cyber victimization. 44 Thus, when compared to the general population, people with IDD are more often victims of crime and abusive incidents. 45 In addition, fears associated with victimization and exploitation are significant concerns for people with IDD and their families.…”
Section: Victimization and Safetymentioning
confidence: 99%